Race, empire and First World War writing - Das, Santanu (Cambridge ; New York : Cambridge University Press, 2011)
"This volume brings together an international cast of scholars from a variety of fields to examine the racial and colonial aspects of the First World War and show how issues of race and empire shaped its literature and culture. The global nature of the First World War is fast becoming the focus of intense enquiry. This book analyses European discourses about colonial participation and recovers the war experience of different racial, ethnic and national groups, including the Chinese, Vietnamese, Indians, Maori, West Africans and Jamaicans. It also investigates testimonial and literary writings - from war diaries and nursing memoirs to Irish, New Zealand and African American literature - and analyses processes of memory and commemoration in the former colonies and dominions. Drawing upon archival, literary and visual material, the book provides a compelling account of the conflict's reverberations in Europe and its empires and reclaims the multiracial dimensions of war memory"--
Machine generated contents note: Introduction Santanu Das; Part I. Voices and Experiences: 1. 'An army of workers': Chinese indentured labour in First World War France Paul J. Bailey; 2. Sacrifices, sex, race: Vietnamese experiences in the First World War Kimloan Hill; 3. Indians at home, Mesopotamia and France, 1914-1918: towards an intimate history Santanu Das; 4. 'We don't want to die for nothing': Askari at war in German East Africa, 1914-1918 Michelle Moyd; 5. France's legacy to Demba Mboup? A Senegalese Griot (and his descendants) remember his military service during the First World War Joe Lunn; Part II. Perceptions and Proximities: 6. Representing Otherness: African, Indian, and European soldiers' letters and memoirs Christian Koller; 7. Living apart together: Belgian civilians and non-European troops and workers in wartime Flanders Dominiek Dendooven; 8. Nursing the Other: the representation of colonial troops in French and British First World War nursing memoirs Alison S. Fell; 9. Imperial captivities: colonial prisoners of war in Germany and the Ottoman Empire, 1914-1918 Heather Jones; 10. Images of Te Hokowhitu A Tu in the First World War Christopher Pugsley; Part III. Nationalism, Memory and Literature: 11. 'He was black, he was a white man, and a dinkum Aussie': race and empire in revisiting the Anzac legend Peter Stanley; 12. The quiet Western Front: the First World War and New Zealand memory Jock Phillips; 13. 'Writing out of opinions': Irish experience and the theatre of the First World War Keith Jeffery; 14. 'Heaven grant you strength to fight the battle for your race': nationalism, Pan-Africanism and the First World War in Jamaican memory Richard Smith; 15. Not only war: the First World War and African American literature Mark Whalan; Afterword: death and the afterlife: Britain's colonies and dominions Michèle Barrett.
Includes bibliographical references and index.
Keywords: World War, 1914-1918 -- Social aspects; World War, 1914-1918 -- Historiography; Imperialism; Indigenous peoples; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; Europe -- Armed Forces -- Colonial forces -- History -- 20th century; Europe -- Colonies -- Race relations -- History -- 20th century; Europe -- Colonies -- History -- 20th century